Purchasing sustainable palm oil products: narrowing the intention-behavior gap - Sundaraja, Cassandra Shruti; Lykins, Amy Dianne; Hine, Donald William (Frontiers in Nutrition, 2024)
Experts on palm oil production and utilization emphasize the role of consumer purchasing power in dealing with the environmental and social impacts of the palm oil crisis -that by increasing the demand for sustainable palm oil (SPO), greater supply will follow. However, research has identified a persistent intention-behavior gap. Even knowledgeable consumers do not always follow through on their intentions to purchase SPO. Utilizing the Capability-Opportunity Motivation model of Behavior (COM-B), this article reviews important variables contributing to this intention-behavior gap. While knowledge about palm oil and SPO (capability), perceived product availability (opportunity), and progreen consumption attitudes (motivation) are important predictors of SPO purchasing intentions, increasing these factors has been insufficient in narrowing the intention-behavior gap. Campaigns can increase knowledge about palm oil and SPO, as well as build motivation around making the 'sustainable' choice, but are inadequate in addressing barriers around opportunity (e.g., ease of access to SPO products). In expressing their intent to purchase SPO products, consumers may underestimate the difficulties in being able to identify these consumables (e.g., palm oil often is not clearly labeled, sustainability status may not be obvious), and locate them. In this review, we argue that while consumer behavior is important, it is insufficient to power industry-wide change towards the utilization of SPO. Greater corporate responsibility is needed to increase use of SPO in products, and make consumables containing SPO more available, identifiable, and affordable for consumers. We also suggest that national procurement policies for SPO are likely to produce longer-lasting change.